Konsep Keadilan Voting dalam Rapat Penundaan Kewajiban Pembayaran Utang - yalid yalid; Irawan Harahap; Riantika Pratiwi (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2023)
Purpose: To explain the contradictions of the reconciliation arrangement in the meeting voting on the Debt Payment Obligation Deferral and to formulate the concept of ideal justice voting in the Debt Payment Obligation Deferral meeting. Research methodology: This type of research is normative legal research. Results: The principle of justice in the Bankruptcy and PKPU Laws contains that provisions regarding bankruptcy can fulfill a sense of justice for interested parties. The entire analysis of the concept of justice is related to legal facts in the Bankruptcy Law and PKPU which adopt the principle of balance by stating that the principle of